Marital satisfaction's profile of Singapore couples - Leong, Yoke Yin. (2008)
This study examined the marital relationships of 15 Singapore couples. The ENRICH inventory was administered to assess the level of satisfaction on 11 areas: marital satisfaction, personality issues, communication, conflict resolution, financial management, sexual relationship, role relationship, family and friends, leisure activities, children and parenting, and spiritual beliefs. Interviews were conducted for each of the 15 couples to gain further insights into the marital processes. The profiles of the 5 types of marital relationships - vitalised, harmonious, traditional, conflictual, and devitalised were described.